+0  
 
+1
142
1
avatar+164 

4) For the sum -10 -13 -16 -... -43:

 

(a) Rewrite the sum using summation notation (\(\sum\)).

 

(b) Evaluate the sum.

 Nov 23, 2019
 #1
avatar+109334 
+2

(a)  

    12

    ∑    -7 - 3n

n  = 1

 

Note that other forms are possible.....

 

(b)  The sum can be found as

 

[ First Term + Last Term ] *  [ Number of terms] / 2

 

The number of terms is   [  43 - 10 ] / 3  + 1 =   33/3 + 1 =  11 + 1 = 12

 

So....the sum is

 

[ -10 + -43 ] * [ 12 / 2]  =

 

] -53] * 6  =

 

-318

 

cool cool cool

 Nov 23, 2019

21 Online Users

avatar
avatar
avatar